An Exploratory Study of the Risks and Benefits of Speculative Business from the Perspectives of the Muslim Community - Abba Alhaji Bukar; Wakil Mala Bukar; Bintu Mustapha; Maga Sule (Maddah: Journal of Advanced Da'wah Management Research, 2026)
Speculative business has become increasingly prominent in modern economies, particularly in stock markets, derivatives, foreign exchange, and cryptocurrencies. While such activities may enhance market liquidity and price discovery, they also pose significant ethical, economic, and social risks. From an Islamic perspective, all economic activities must comply with Shari’ah principles that emphasise justice, transparency, and societal welfare. This study aims to examine the risks and benefits of speculative business within the framework of Islamic jurisprudence by analysing its compatibility with the prohibitions of ribā, gharar, and maysir, as well as the broader objectives of maqāṣid al-Sharīʿah and maṣlaḥah (public interest). The research employs a qualitative desk-review methodology, systematically analysing classical fiqh al-muʿāmalāt texts, primary Shari’ah sources, and contemporary literature on modern financial instruments. The findings indicate that although speculation can contribute to market efficiency and innovation when conducted responsibly and within ethical boundaries, it frequently leads to excessive volatility, wealth inequality, market instability, and violation of core Shari’ah principles. The study concludes by proposing viable Shari’ah-compliant alternatives—such as mushārakah, muḍārabah, and asset-backed investments—that balance risk-taking with ethical responsibility and real economic productivity.